News in breast oncology genetics for female and male population - Taris, Nicolas; Luporsi, Elisabeth; Osada, Marine; Thiblet, Marie; Mathelin, Carole (Gynécologie, obstétrique, fertilité & sénologie, 2024)
Breast oncology genetics emerged almost 30 years ago with the discovery of the BRCA1 and BRCA2 genes. The evolution of analytical practices has progressively allowed access to tests whose results now have a considerable impact on the management of both female and male breast cancers. The Sénologie commission of the Collège national des gynécologues et obstétriciens français (CNGOF) asked five specialists in breast surgery, oncology and oncological genetics to draw up a summary of the oncogenetic testing criteria used and the clinical implications for the female and male population of the test results, with or without an identified causal variant. In the case of proven genetic risk, surveillance, risk-reduction strategies, and the specificities of surgical and medical management (with PARP inhibitors in particular) were updated. This summary was based on national and international guidelines on the monitoring and therapeutic management of genetic risk, and a recent review of the literature covering the last five years. Despite successive technical developments, the probability of identifying a causal variant in a situation suggestive of a predisposition to breast and ovarian cancer remains around 10% in France. The risk of breast cancer in women with a causal variant of the BRCA1, BRCA2, PALB2, TP53, CDH1 and PTEN genes is estimated at between 35% and 85% at age 70. The presence of a causal variant in one of these genes is the subject of different recommendations for men and women, concerning both surveillance, the age of onset and imaging modalities of which vary according to the genes involved, and risk-reduction surgery, which is possible for women as soon as their risk level exceeds 30% and remains exceptionally indicated for men. In the case of breast cancer, PARP inhibitors are a promising new class of treatment for BRCA germline mutations. A discipline resolutely focused on understanding molecular mechanisms, screening and preventive medicine/surgery, oncology genetics is currently also involved in new medical/surgical approaches, the long-term benefits/risks of which will need to be monitored.